2020
DOI: 10.1055/s-0040-1715641
|View full text |Cite
|
Sign up to set email alerts
|

From Anti-EBV Immune Responses to the EBV Diseasome via Cross-reactivity

Abstract: Sequence analyses highlight a massive peptide sharing between immunoreactive Epstein-Barr virus (EBV) epitopes and human proteins that—when mutated, deficient or improperly functioning—associate with tumorigenesis, diabetes, lupus, multiple sclerosis, rheumatoid arthritis, and immunodeficiencies, among others. Peptide commonality appears to be the molecular platform capable of linking EBV infection to the vast EBV-associated diseasome via cross-reactivity and questions the hypothesis of the “negative selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 179 publications
(236 reference statements)
0
17
0
Order By: Relevance
“…Molecular mimicry and epitope spreading are classical, well-documented mechanisms of autoimmunity induction, as confirmed in a recent study which showed massive peptide sharing between EBV epitopes and human proteins [ 15 ].…”
Section: General Mechanisms Of Virus-induced Autoimmunitymentioning
confidence: 90%
See 2 more Smart Citations
“…Molecular mimicry and epitope spreading are classical, well-documented mechanisms of autoimmunity induction, as confirmed in a recent study which showed massive peptide sharing between EBV epitopes and human proteins [ 15 ].…”
Section: General Mechanisms Of Virus-induced Autoimmunitymentioning
confidence: 90%
“…Molecular mimicry Viral antigens with structural similarity with self-antigens can be presented to and activate autoreactive T-lymphocytes. [8,9,[14][15][16][17][18] Epitope-spreading Over time, persistent viral infection elicits autoantibodies directed not only towards initial antigens but also multiple epitopes of the same antigens or even different antigens, increasing breadth of immune response.…”
Section: Mechanism Description Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, vaccine-induced autoimmunity from autoimmune cross-reactivity is associated with several pathologies including Guillain-Barré syndrome, multiple sclerosis, demyelinating neuropathies, systemic lupus erythematosus, narcolepsy, or postural orthostatic tachycardia syndrome in susceptible subgroups [ 51 ]. Therefore, one of the side effects of introducing a mass vaccination program could be an emergence of autoimmune diseases especially in individuals who are genetically prone for autoimmunity [ 52 , 53 , 54 ]. The composition of SARS-CoV-2 proteins and validation of similarities with human proteins are critical to predict an autoimmune response associated with immunity against host proteins and its clinical manifestations as well as potential adverse effects of vaccination [ 55 ].…”
Section: Raised Concerns Of Current Sars-cov-2 Vaccinesmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Pathologically, cross-reactions between pathogen and human proteins might lead to thrombocytopenia, altered spermatogenesis, schizophrenia and neuropsychiatric diseases, neurodegeneration, lymphomas, sudden death, microcephaly and Guillain-Barré syndrome, pneumonia, multiple sclerosis, immunodeficiency, developmental disorders, autoinflammatory disease, arthritis, hemochromatosis, myasthenia gravis, and systemic lupus erythematosus. 4,8,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] As a matter of fact, pathogen-derived immunoreactive epitopes are mostly composed of peptide sequences present in human proteins, 10,18,21,23,26 thus documenting that the immune system does not exert any negative selection of selfreactive lymphocytes. 27,28 Hence, it comes as a logical consequence that peptide sharing between infectious antigens and human proteins can cause cross-reactions in the human host, possibly leading to a multitude of postinfection autoimmune pathologies.…”
Section: Introductionmentioning
confidence: 99%